Estudio de factibilidad técnico – Económico para la instalación de un larvario – Laboratorio productor de semilla de camarón gigante de agua dulce, en la provincia de San Martín - Arce Saavedra, Thony (1995)
The seed (Postlarvae) of shrimp giant of water sweet that is produced currently in the country, not meets in quantity or in quality to the market national; more still exist growing expectation for this culture marked by its profitability and the final market. The demand of the market internal is unsatisfied in 21.70 T.M. (48.20), such as shrimp fresh frozen (1994); with the particularity that the demand increases with the growth of production. With the knowledge of the exceptional conditions of water, soil and climate to develop the Canary on a large scale, as a real alternative to displace the Coca cultivation in the forest; and, to determine the real need for seed and partly to satisfy the market, as well as establish technology appropriate for commercial production; the present study which required the installation of a Larvario financial and economic possibility arose. In the region San Martín for 1995 only a 20.25%...